Evaluation of RAS Mutational Status in Liquid Biopsy to Monitor Disease Progression in Metastatic Colorectal Cancer Patients - Elena Lastraioli; Alessandra Bettiol; Jessica Iorio; Elvira Limatola; Daniele Checcacci; Erica Parisi; Cristina Bianchi; Annarosa Arcangeli; Mauro Iannopollo; Francesco Di Costanzo; Marco Di Lieto (Cells, 2023)
In this study we evaluated both~ K- and N-RAS mutations in plasma samples from patients with metastatic colorectal cancer by means of the BEAMing technology, and we assessed their diagnostic performance compared to RAS analyses performed on tissue. The sensitivity of BEAMing in identifying KRAS mutations was of 89.5%, with a fair specificity. The agreement with tissue analysis was moderate. The sensitivity for NRAS was high with a good specificity, and the agreement between tissue analysis and BEAMing was fair. Interestingly, significantly higher mutant allele fraction (MAF) levels were detected in patients with G2 tumors, liver metastases, and in those who did not receive surgery. NRAS MAF level was significantly higher in patients with mucinous adenocarcinoma and for those with lung metastases. A sharp increase in the MAF values was observed in patients who moved towards disease progression. More strikingly, molecular progression always anticipated the radiological one in these patients. These observations pave the way to the possibility of using liquid biopsy to monitor patients during treatment, and to enable oncologists to anticipate interventions compared to radiological analyses. This will allow time to be saved and ensure a better management of metastatic patients in the near future.